System evaluation and Meta analysis on clinical efficacy of heat-sensitive moxibustion in treatment of cervical spondylotic radiculopathy - ZHANG, Yang; ZHOU, Mei-qi; TANG, Wei; SONG, Xiao-ge (World journal of acupuncture-moxibustion, 2016)
To systematically evaluate the efficacy of heat-sensitive moxibustion in treatment of cervical spondylotic radiculopathy (CSR). Chinese National Knowledge Infrastructure (CNKI), China Biology Medical (CBM) database, Chinese Science and Technology Periodical Database (VIP), WanFang Data, Pubmed and Cochrane Library were retrieved to search the randomized controlled trials (RCT) on heat-sensitive moxibustion in treatment of CSR, and Meta analysis was conducted by applying RevMan 5.3 software. Eventually, 10 papers were included in this study, including 1008 subjects. Meta analysis result showed: the total effective rate of treatment group was higher than that of control group, and the difference was statistically significant [RR = 1.13, 95%CI(1.06, 1.21), Z=3.54, P=0.000 4]; the cure rate of treatment group was higher than that of control group, and the difference was statistically significant [RR=1.80, 95%CI(1.52, 2.13), Z=6.82, P<0.000 01]; the improvement of short-form McGill pain questionnaire (SF-MPQ) of treatment group was superior to that of control group, and the difference was statistically significant [MD=−4.44, 95%CI(–6.38, −2.50), Z=4.49, P<0.000 01]; visual analogue scale (VAS) of treatment group was lower than that of control group, and the difference was statistically significant [MD=−0.36, 95%CI(−0.50, –0.23), Z=5.42, P<0.00001]; and the improvement of interleukin-6 (IL-6) of treatment group was superior to that of control group, and the difference was statistically significant [MD=−7.32, 95%CI(−11.49, –3.14), Z=3.44, P=0.000 6]. It is indicated from the Meta analysis result that the clinical efficacy of heat-sensitive moxibustion or acupuncture combined with heat-sensitive moxibustion in treatment of CSR is superior to that of simple acupuncture or traditional suspended moxibustion, providing a new therapeutic method for treatment of CSR. However, the abovementioned conclusion still needs to be confirmed through randomized blind controlled trials with high quality and large sample size since the sample size of included studies was small, and the quality was low.